In defense of (extreme) monism - Garner, Jeremy (2016)
There are broadly speaking two varieties of views regarding the nature of coincident entities such as statues and the pieces of matter which constitute them. According to Monists, (some) coincident entities are identical while according to pluralists coincident entities are always distinct. The aim of this thesis is to defend the view that many cases of coincidence, including cases of temporary coincidence, are instances of identity. First, I will argue that pluralism ought to be rejected because it faces serious philosophical challenges monism avoids. Next, I will argue that monism can adequately resist the three most common Leibniz law arguments levied against the plausibility that (some) coincident objects are identical. Specifically I will argue that the best monist response to the modal Leibniz law is to adopt a counterpart theoretic account of de re modality to justify the claim that modal contexts are referentially opaque. Next, I will show how monists can resist the linguistic version of LLA by either denying the truth (or falsity) of one of the relevant premises, or by denying the validity of the argument in question. Finally I will argue that the best monist response to the temporal version of LLA is to adopt a stage theoretic account of persistence which can offer a unified account of what Michael Rea has called the “the problems of material constitution.”